A kontaktimprovizáció definiálása - Gál, Eszter (Symbolon, 2021)
Defining Contact Improvisation What happens when two moving people touch each other and focus on the sensations of gravity, the Earth and their partner (Lepkoff 2000, 61)? Can this question lead to one of the definitions of Contact Improvisation? What are those principles that keep the practitioners’ curiosity to investigate the dance form even today? Can the embodied knowledge of CI be seen or read in a composed movement? In this paper, I summarize the forming and development of Contact Improvisation from 1972, including its instigators. I also give an overview of its possible definitions by articulating its basic principles as a movement technique and highlighting its embedded presence in the American postmodern dance area as a performance form. I touch upon its appearance in Hungary and by a short photo analyzation I intend to illustrate the key elements of the technique to get closer to understanding this emerging dance form.